The sex peptide receptor in the Asian gypsy moth, Lymantria dispar, is involved in development and stress resistance - Hui DU; Li-li SUN; Peng LIU; Chuan-wang CAO (Journal of Integrative Agriculture, 2021)
The G protein-coupled receptor (GPCR) regulates downstream genes by binding to a heterotrimeric G protein. However, the function of sex peptide receptor (SPR) in lepidopteran species is mostly unknown. Understanding the physiological functions of SPR in insects is essential for exploring new insecticidal targets. In the present study, the functions of an SPR in Lymantria dispar (Asian gypsy moth; LdSPR) were investigated. The expression of LdSPR was the highest in the 6th instar larval stage, and there was a large difference in expression between male and female adults. After LdSPR gene silencing, L. dispar larvae showed increased sensitivity to high temperature, starvation, and oxidative stress, indicating that LdSPR enhances stress resistance. These results enrich our knowledge of the function of the insect SPRs, which will lead to a better understanding of other insect GPCR family members and the identification of new targets for the development of environmentally friendly pesticides.